The Effect of Fruit Consumption Time on Glucose Regulation in Pregnancy With Gestational Diabetes - NAS, SEVİL; Yılmaz, Hande Öngün (Pontificia Universidade Catolica Campinas, 2023)
ObjectiveThis study aims to determine the effect of fruit consumption time on blood glucose regulation in pregnant women with gestational diabetes.MethodsThe study was carried out with 64 volunteer participants diagnosed with gestational diabetes. Participants who were directed to the Department of Nutrition and Dietetics were divided into two groups according to the order of application; Group 1 was included in the nutrition treatment program for a week, consuming fruit for the main meal and Group 2 for the snack. During this process, the participants were applied a personalized nutrition plan that was adjusted equally for macronutrients of all meals containing isocaloric 3 main and 4 snacks. In this process, blood glucose values were measured six times a day by the participants and the blood glucose results of both groups before starting the nutrition therapy and on the seventh day after starting the medical nutrition therapy were compared.ResultsThe mean age of the women participating in the study was 33.50 +/- 4.95 years and 32.28 +/- 5.18 years for the 1st and 2nd groups, respectively, and the groups were similar in terms of anthropometric measurements. The post-diet average of postprandial blood glucose levels in the morning within each group dropped from 180mg/d to 115mg/dL (p<0,001) for Group 1 and from 185mg/dL to 110mg/dL (p<0,001) for Group 2. There was a decrease in the fasting plasma glucose and postprandial blood glucose levels measured in the morning, noon and evening before and after the medical nutrition therapy of the groups, but no statistically significant difference was found between the groups (p>0.05). All participants on the gestational diabetes diet had normal blood sugar levels without the need for insulin. A statistically significant decrease was observed in the postprandial blood glucose-fasting plasma glucose difference levels of the pregnant women in the group that consumed fruit for snacks (Group 2) on the seventh day of the study (p<0,001). There was no significant difference in the pre-diet and post-diet morning fasting plasma glucose values of both groups (p>0,05).ConclusionThis study found that medical nutrition therapy in pregnant women with gestational diabetes led to a decrease in blood glucose levels, but consuming fruits as a snack or at the main meal did not make a significant difference on fasting plasma glucose and postprandial blood glucose. It was concluded that the type and amount of carbohydrates consumed daily in gestational diabetes are determinative on blood glucose level.

RESUMO Objetivo O objetivo deste estudo é determinar o efeito do tempo de consumo de fruta na regulação da glucose no sangue em mulheres grávidas com diabetes gestacional. Métodos Este estudo foi realizado com 64 participantes voluntários diagnosticados com diabetes gestacional. Os participantes que foram encaminhados para o Departamento de Nutrição e Dietética foram divididos em dois grupos, de acordo com a ordem da sua aplicação. O grupo 1 foi incluído no programa de tratamento médico nutricional durante uma semana, consumindo fruta para a refeição principal e o grupo 2 para os lanches. Neste processo, foi aplicado aos participantes um plano de nutrição personalizado, com isocalórico, 3 refeições principais e 4 lanches, os macronutrientes de todas as refeições foram ajustados igualmente. Neste processo, os valores de glicemia foram medidos seis vezes por dia pelos participantes, e foram comparados os resultados da glicemia de ambos os grupos antes de se iniciar a terapia nutricional médica e no sétimo dia após o início da terapia nutricional médica. Resultados A idade média das mulheres que participaram no estudo foi de 33,50±4,95 e 32,28±5,18 anos para o 1º e 2º grupos, respetivamente, e não houve diferença entre os grupos em termos de medidas antropométricas. A glicemia média pós-prandial de manhã após terapia nutricional médica dentro dos grupos variou entre 180mg/d a 115mg/dL (p<0,001) para o Grupo 1, e de 185mg/dL a 110mg/dL para o Grupo 2 (p<0,001). Houve uma diminuição nos níveis de glicemia em jejum e glicemia média pós-prandial medidos de manhã, meio-dia e noite antes e depois da terapia nutricional médica dos grupos, mas não houve diferença estatisticamente significativa entre os grupos (p>0,05). Os níveis de açúcar no sangue de todos os participantes na dieta diabetes gestacional baixaram para níveis normais sem necessidade de terapia com insulina. Uma diminuição estatisticamente significativa foi observada no sétimo dia do estudo nos níveis de diferença do glicemia média pós-prandial-glicemia em jejum das mulheres grávidas do grupo que consumiram fruta como aperitivo (Grupo 2). (p<0.001). Não houve diferença significativa nos valores de glicemia em jejum matinal de ambos os grupos antes e depois da dieta (p>0,05). Conclusão Como resultado deste estudo, verificou-se que a terapia nutricional levou a uma diminuição do açúcar no sangue em mulheres grávidas com diabetes gestacional, mas o consumo de fruta como lanche ou refeição principal não fez uma diferença significativa no jejum e na glucose do sangue pós-prandial. Concluiu-se que o tipo e a quantidade de hidratos de carbono consumidos diariamente na diabetes gestacional são determinantes para o nível de glicose no sangue.
O efeıto do tempo de consumo de fruta na regulação da glıcose na gravıdez com dıabetes gestacıonal
Keywords: Diabetes; Gestational; Fructose; Fruit; Glycemic Index